A coupled data assimilation system for climate reanalysis. (24th September 2015) - Laloyaux, Patrick; Balmaseda, Magdalena; Dee, Dick; Mogensen, Kristian; Janssen, Peter
Abstract : A coupled data assimilation system has been developed at the European Centre for Medium‐Range Weather Forecasts (ECMWF), which is intended to be used for the production of global reanalyses of the recent climate. The system assimilates a wide variety of ocean and atmospheric observations and produces ocean–atmosphere analyses with a coupled model. Employing the coupled‐model constraint in the analysis implies that assimilation of an ocean observation has immediate impact on the atmospheric state estimate and, conversely, assimilation of an atmospheric observation affects the ocean state. This covariance between atmosphere and ocean induced by the analysis method is illustrated with simple numerical experiments. Realistic data assimilation experiments based on the global observing system are then used to assess the quality of the assimilation method. Comparison with an uncoupled system shows a mostly neutral impact overall, with slightly improved temperature estimates in the upper ocean and lower atmosphere. These preliminary results are considered of interest for the ongoing community efforts focusing on coupled data assimilations.